Pembelajaran Kosakata dan Kemampuan Berbahasa terhadap Anak Tunagrahita - Fathiyah Al Khairiyyah; Indah Murni Ramadani; Suci Izati Syahidah; Zelda Shakila Zivanka; Siti Hamidah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Vocabulary learning is the initial learning so that children have the ability to read and speak. However, there are some children who have barriers to developing their language skills, one of which is children with disabilities. The obstacle is caused by their low intelligence so that it is difficult to understand and record information related to language, both understanding vocabulary and the ability to pronounce it as well as limited media that support the learning process. Therefore, a more effective way of improving language skills for children with disabilities is needed so that they do not fall behind other children. This research aims to find effective learning methods in developing language skills in children with disabilities. Using the Systematic Literature Review (SLR) research method by reviewing and identifying previous research related to language development in children with disabilities, various supportive learning methods were found such as music therapy, anagram games, role play methods, picture crosswords, visuomotor learning methods, storytelling, and card media.